Japan’s Giga School Program: Equips Students with Life Skills for Digital - Adriani, Sri Dewi (PT Mattawang Mediatama Solution, 2025)
The Covid 19 pandemic is a human tragedy impacting all life aspects. One of them is education. In Japan, several policies were implemented to address gaps in access to education due to school closures during the pandemic. This article aims to describe the policy of the Japanese government in building a distance learning system that can be accessed equally by all students. This policy is known as The Global and Innovation Gateway for All (GIGA)'s school program. This program carries the concept of